Геодезические работы в строительстве - Ганьшин В. Н. Владимир Николаевич; Коськов Б. И. Борис Иванович; Бородулин Г. И. Герман Иванович; Котков А. В. Анатолий Васильевич; Зимин К. И. Константин Иванович (Справочник строителя)
Авт. указ. на обороте тит. л.